13‐valent pneumococcal conjugate vaccine (PCV13) is immunogenic and safe in children 6‐17 years of age with sickle cell disease previously vaccinated with 23‐valent pneumococcal polysaccharide vaccine (PPSV23): Results of a phase 3 study. Issue 8 (23rd March 2015) - De Montalembert, Mariane; Abboud, Miguel R.; Fiquet, Anne; Inati, Adlette; Lebensburger, Jeffrey D.; Kaddah, Normeen; Mokhtar, Galila; Piga, Antonio; Halasa, Natasha; Inusa, Baba; Rees, David C.; Heath, Paul T.; et al.
<x xml:space="preserve">Abstract</x> Background A large population of older children with sickle cell disease (SCD) is currently vaccinated with only 23‐valent pneumococcal polysaccharide vaccine (PPSV23). In immunocompetent adults, PPSV23 vaccination reduces immune responses to subsequent vaccination with a pneumococcal vaccine. The 13‐valent pneumococcal conjugate vaccine (PCV13), which addresses this limitation, may offer an advantage to this population at high risk of pneumococcal disease. Procedure Children with SCD 6–17 years of age previously vaccinated with PPSV23 at least 6 months before study enrollment received two doses of PCV13 6 months apart. Anti‐pneumococcal polysaccharide immunoglobulin G (IgG) geometric mean concentrations (GMCs) and opsonophagocytic activity (OPA) geometric mean titers (GMTs) were measured before, 1 month after each administration, and 1 year after the second administration. Results Following each PCV13 administration, IgG GMCs and OPA GMTs significantly increased, and antibody levels after doses 1 and 2 were generally comparable. Antibody levels declined over the year following dose 2. At 1 year after the second administration, OPA GMTs for all and IgG GMCs for most serotypes remained above pre‐vaccination levels. Most adverse events were due to vaso‐occlusive crises, a characteristic of the underlying condition of SCD. Conclusions Children with SCD who were previously vaccinated with PPSV23 responded well to 1 PCV13 dose, and a second dose did not increase antibody response. PCV13 antibodies persisted above pre‐vaccination levels for all serotypes 1 year after dose 2. Children with SCD may benefit from at least one dose of PCV13. Pediatr Blood Cancer 2015;62:1427–1436. © 2015 Wiley Periodicals, Inc.